2011
DOI: 10.4103/0973-029x.86693
|View full text |Cite
|
Sign up to set email alerts
|

"Hybrid" lesion of the maxilla

Abstract: Juvenile ossifying fibroma is an uncommon benign but aggressive fibroosseous lesion that affects the craniofacial skeleton. Their distinct clinical and histopathological features warrant the lesion to be considered as a separate entity from other fibro-osseous group of lesions such as fibrous dysplasia and cemento ossifying fibroma. Concomitant development of secondary aneurysmal bone cyst may rarely occur, which makes the lesion more aggressive and difficult to treat. We report a case of a 6 year old girl who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Silva et al [13] reported a case of TrJOF associated with ABC involving the left maxilla. Sankaranayaran et al [14] have highlighted a recurrent case of in which an association of TrJOF was diagnosed when the lesion recurred.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva et al [13] reported a case of TrJOF associated with ABC involving the left maxilla. Sankaranayaran et al [14] have highlighted a recurrent case of in which an association of TrJOF was diagnosed when the lesion recurred.…”
Section: Discussionmentioning
confidence: 99%
“…The aggressive nature of this entity with high rates of recurrence (30-50%) suggests that TrJOF with development of a secondary ABC should be treated with radical surgical resection, rather than conservative curettage. [8,[12][13][14] The prognosis is good because malignant changes and metastases have not been reported. [10] Radiotherapy is contraindicated because of the risk of possible malignant transformation and potential harmful late effects of growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other entities that may manifest clinically as tumors in the maxillofacial area, with or without affectation to the neighboring teeth and appearing as radiolucent images in imaging tests (13-15) should be included in the differential diagnosis of fibro-osseous lesions. Some examples are central giant-cell granuloma, brown tumor of hyperparathyroidism, cherubism, aneurysmal bone cyst, intraosseous vascular malformations, Langerhans cell histiocytosis, non-odontogenic cysts (globulomaxilar cyst, nasolabial cyst, central mandibular cyst, nasopalatine duct cyst) and neurogenic tumors (Schwannoma, neurofibroma and traumatic neuroma).…”
Section: Discussionmentioning
confidence: 99%
“…Hematological manifestations are quite late and patients may present with microcytic hypochromic anemia, bicytopenia or pancytopenia [2]. A high index of clinical suspicion, radiological and hematological correlation is a must for early diagnosis and proper management [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%